DIGITAL FORENSIC INVESTIGATION ON STORAGE MEDIA BASED ON NIST WITH FORENSIC PROCESS METHODS - Indra Gunawan; Heru Satria Tambunan; Abdullah Ahmad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2026)
Abstract: Storage media is an inseparable tool in everyday life. With storage media, users can store important data, both personal and workplace. In addition, in many cases, Indonesian law uses storage media as evidence. The Electronic Information and Transactions Law (UU ITE) regulates how the provision of digital evidence can be strong evidence in court. This study examines the forensics of digital evidence on storage media with four test scenarios. Digital forensic processing uses forensic processes based on the National Institute of Standards and Technology (NIST) guidelines. This study produces an analysis in which evidence processed with scenarios 1 and 4 is valid digital evidence to be submitted to court, while evidence 2 and 3 is invalid evidence. The results of this digital evidence can be used for investigations under the ITE law. Keywords: autopssy; digital forensics; storage media; FTK Imager. Abstrak: Media Penyimpanan merupakan alat yang tak terpisahkan dari kehidupan sehari-hari. Dengan Media Penyimpanan, pengguna dapat menyimpan data penting, baik pribadi maupun tempat kerja. Selain itu, dalam banyak kasus, hukum Indonesia menggunakan Media Penyimpanan sebagai alat bukti. Undang-Undang Informasi dan Transaksi Elektronik (UU ITE) mengatur bagaimana penyediaan alat bukti digital menjadi alat bukti yang kuat di pengadilan. Penelitian ini mengkaji forensik terhadap alat bukti digital pada Media Penyimpanan dengan empat skenario pengujian. Pemrosesan forensik digital menggunakan proses forensik berdasarkan panduan National Institute of Standards and Technology (NIST). Penelitian ini menghasilkan analisis di mana alat bukti yang diproses dengan skenario 1 dan 4 merupakan alat bukti digital yang sah untuk diajukan ke pengadilan, sedangkan alat bukti 2 dan 3 merupakan alat bukti yang tidak sah. Hasil dari barang bukti digital ini, dapat digunakan untuk penyelidikan didalam undang-undang ITE. Kata kunci: otopsi; forensik digital; media penyimpanan; FTK Imager